(untitled) (Journal of the College of Basic Education, 2023)
This research includes a study of the effect of using a laser (helium-cadmium) with a wavelength of 441.6 nm and a laser output power of (10 mW), which is a gas laser with low power [LPLA] operating in continuous mode (CW) on improving the efficiency of defective silicon solar cells. As a result of use, the basic parameters of the output of the solar cell were studied, through which the efficiency of the solar cell is determined, represented by the electrical characteristics in the case of light and dark before and after the laser treatment of the samples and for different periods of time to reach the state of stability. In the case of darkness, the study showed that the laser treatment does not cause a clear effect on the efficiency of the cell, as it was noted that there was no significant effect on the density of the reverse saturation current Jo and the ideal factor n of the silicon solar cell by studying the characteristics of (J-V) in the dark case, but in the case of light, the characteristics of (J-V) of the solar cell improved by observing a significant increase in the values of each of the open circuit voltage, short circuit current density Jsc, output power Pmax, as well as the filling factor F.F, which indicates a high efficiency of the defective solar cell as a result of use.